Saudi Arabia: Between Radicalisation and Terrorism - Nidaa Abu-Ali (2016)
The threat of a terrorist attack inside Saudi Arabia has diminished since the government began taking measures to make the environment more hostile to terrorist networks. Instead Saudi militants are travelling to other conflict zones to fight.